Fractures of the anterior process of the calcaneum; a review and proposed treatment algorithm. Issue 3 (June 2019) - Dhinsa, Baljinder S.; Latif, Ahmed; Walker, Roland; Abbasian, Ali; Back, Diane; Singh, Sam
Highlights: Delay in diagnosis is common and has a negative impact on outcome. High index of suspicion with an accurate history and examination. If plain radiographs are inconclusive, CT/MRI is required. Undisplaced/minimally displaced fractures managed initially non-operatively. Acute surgical intervention indicated for large type III fractures. Abstract: Background: There remains a lack of recognition of these fractures, which leads to a delay in diagnosis and appropriate management. Methods: A comprehensive literature search was performed. Following inclusion and exclusion criteria, 23 studies were available for analysis. Results: Delay in diagnosis is common and has a negative impact on outcome. If an APC fracture is suspected; anteroposterior, lateral and oblique plain radiographs should be requested. Further investigation with computed tomography or magnetic resonance imaging is indicated if plain radiographs are inconclusive and patient remains symptomatic. Non-operative measures are usually adequate for most undisplaced fractures, however surgical intervention maybe required for large, intra-articular fractures in the acute setting and for non-union. Conclusions: A treatment algorithm is suggested that may help with the diagnosis and management of these injuries. Level of evidence: Level IV.